Volume 9: Seismic Engineering 2020
DOI: 10.1115/pvp2020-21226
|View full text |Cite
|
Sign up to set email alerts
|

Passive Control Techniques for Seismic Protection of Chemical Plants

Abstract: Seismic damage of chemical plant facilities (pressure vessels, piping, storage tanks, etc..) can causes human and economic losses as well as heavy environmental damages. Therefore, it is of paramount importance to reduce such a consequences. The passive control techniques (PCT) as dampers or base isolation can represent an effective technique to mitigate the major damage caused by earthquakes. Viscous dampers, tuned mass dampers and base isolators are well-known passive control devices successfully applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was also found that the percentage reduction in the natural frequency of the impulsive mode remains constant in cases where the conical tank with a slope angle of 30 degrees and 45 degrees, while for tanks with a slope angle of 50 degrees is less. Passive control techniques for seismic protection of chemical plans were investigated in another study which offered applicability of PCT as mitigation strategy [13][14][15][16][17]. In another study, two full-size reservoirs for buckling behavior under general and local differential settlement were investigated using the FEM software model with non-linear geometric algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the percentage reduction in the natural frequency of the impulsive mode remains constant in cases where the conical tank with a slope angle of 30 degrees and 45 degrees, while for tanks with a slope angle of 50 degrees is less. Passive control techniques for seismic protection of chemical plans were investigated in another study which offered applicability of PCT as mitigation strategy [13][14][15][16][17]. In another study, two full-size reservoirs for buckling behavior under general and local differential settlement were investigated using the FEM software model with non-linear geometric algorithm.…”
Section: Introductionmentioning
confidence: 99%